Suomuuraimen viljelystä - Mäkinen, Yrjö (Suo, 1974)
Summary: On the cultivation of cloudberry.
Keywords: 1970-luku; 1970-talet; lakka (vatukat); marjanviljely; luonnonmarjat; viljely; hjortron; bärodling; vilda bär; odling